Evaluasi penggunaan Obat Tradisional di Kelurahan Lautang Benteng Kabupaten Sidrap - Wahyuni L Ode; Hawa (Universitas STRADA Indonesia, 2021)
This study aims to evaluate the use of traditional medicine in Lautang Benteng Village, Sidrap Regency. Based on the results of the study in accordance with the formulation of the problem, it can be concluded that Evaluation of the Use of Traditional Medicines by the Community based on the Dimensions of the Truth of Materials against Traditional Medicines is 92%, Evaluation of the Use of Traditional Medicines by the Community based on the Dimensions of Dosage Accuracy of Traditional Medicines is 64%, Evaluation of the Use of Traditional Medicines by the Community based on the Dimensions of Timeliness of Use of Traditional Medicines is 52%, Evaluation of the use of traditional medicines by the community based on the dimensions of the accuracy of how to use traditional medicines is 76%, and Evaluation of the use of traditional medicines by the community based on the dimensions of the accuracy of the selection of indications for traditional medicines is 84%.